MARGIN SQUEEZE IN THE U.S. AND THE EU: WHY THEY DIFFER? - Demetrius Yannelis (European Scientific Journal, ESJ, 2015)
Margin squeeze has recently emerged as an important issue in the electronic communications markets in the EU, as many incumbent operators have exercised this strategy in order to foreclose competitive new entrants. The experience in all European cases considered in the literature so far shows the difficulty and complexity faced by the competition enforcement authorities in implementing the appropriate imputation test for the purpose of substantiating an abuse of the dominant position. In the US, some Courts have followed a different approach and some authors do not consider margin squeeze as a stand-alone form of anti-competitive conduct. Recent Court decisions have validated these claims and there is a renewed interest on the question of the usefulness of margin squeeze tests in protecting competition and consumers. In the economic literature, there are two imputation tests that can be applied to demonstrate an abusive margin squeeze. The first test known as the Equally Efficient Operator (EEO) test is based on the costs of the incumbent. The second test known as the Reasonably Efficient Operator (REO) test is based on the costs of the entrant. The aim of the present paper is to analyze these tests and stress their weaknesses as policy tools. In doing so we will compare the different approaches on the issue of margin squeeze by the EU and the US antitrust authorities. Furthermore, we will offer some thoughts on how the margin squeeze problem can be tackled from a dynamic point of view.